2019
DOI: 10.7717/peerj.7543
|View full text |Cite
|
Sign up to set email alerts
|

Genome skimming is a low-cost and robust strategy to assemble complete mitochondrial genomes from ethanol preserved specimens in biodiversity studies

Abstract: Global loss of biodiversity is an ongoing process that concerns both local and global authorities. Studies of biodiversity mainly involve traditional methods using morphological characters and molecular protocols. However, conventional methods are a time consuming and resource demanding task. The development of high-throughput sequencing (HTS) techniques has reshaped the way we explore biodiversity and opened a path to new questions and novel empirical approaches. With the emergence of HTS, sequencing the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 97 publications
17
67
0
1
Order By: Relevance
“…gambiae was sequenced using the Sanger method on PCR amplified fragments 27 and further mitochondrial genomes were slowly sequenced along with whole genome projects. Currently, most studies have been using whole genome sequencing or PCR amplification followed by high throughput sequencing to characterize several mitogenomes at once 22 , 23 , 26 in a wide range of insect species showing promising results to reconstruct mitogenomes 32 , 43 . Here, we performed low-coverage whole genome sequencing to assemble and characterize the mitogenomes from seventeen mosquito species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…gambiae was sequenced using the Sanger method on PCR amplified fragments 27 and further mitochondrial genomes were slowly sequenced along with whole genome projects. Currently, most studies have been using whole genome sequencing or PCR amplification followed by high throughput sequencing to characterize several mitogenomes at once 22 , 23 , 26 in a wide range of insect species showing promising results to reconstruct mitogenomes 32 , 43 . Here, we performed low-coverage whole genome sequencing to assemble and characterize the mitogenomes from seventeen mosquito species.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to generate 16 new draft mitogenomes from Culicidae species belonging to eight different genera. This approach has already been used in other studies demonstrating a cost-effective way to recover mitogenomes for evolutionary studies 32 , 43 46 . Richter et al (2015) 32 suggested that a minimum of 10 million reads are needed to recover mitogenomes with higher coverage breadth and datasets having around 1 million reads usually generate highly incomplete mitogenomes.…”
Section: Discussionmentioning
confidence: 99%
“…The 2G raw data generated abundant DNA sequences of three genomes with high sequencing depth. These high-copy fractions of genomic DNA are beneficial to deal with the complex phylogenetic issues unresolved by the traditional DNA sequence fragments (Straub et al, 2012;Trevisan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the decreased cost of whole-genome sequencing, carrying out large-scale cohort studies of non-human species using assembled genomes is still daunting (1). Low-cost sequencing projects remain an attractive alternative in biodiversity and ecological research (2, 3). Such studies can include a large number of samples sequenced at 1-2× read coverage, often called genome skims (4, 5, 6).…”
Section: Introductionmentioning
confidence: 99%